From the margins: Other forms of Higher Education in Ecuador and Mexico - Vargas Moreno, Paola Andrea (2024)
Maintaining as a central interest the investigation of pedagogical tools and the forms of relationships that are implemented in educational experiences from the margins, recognizing these scenarios as places where transformative potentials in education emerge, this article presents the main characteristics of three higher education initiatives to provide examples of pedagogical alternatives made possible in Ecuador and Mexico: the Intercultural University of the Nationalities and Indigenous Peoples of Ecuador Amawtay Wasi, the University of the Peoples of the South (Guerrero, Mexico) and the Universidad Campesina Indígena en Red (Puebla, Mexico). Theoretically, we distance ourselves from positivist pedagogy to trace processes that have paved the way towards other pedagogies and other possible worlds. Methodologically, our reflections are the result of an ethnographic and autoethnographic research process that allows us to know from within the complexities of educational projects and, at the same time, to narrate our situated pedagogical experiences. Although we find that these universities face significant difficulties (resources, official validity), we also locate the emergence of pedagogical gestures that attempt to respond to local contexts, inaugurate other forms of relationship (with the community, with knowledge, between subjects) and open pedagogical mechanisms that allow naming the world from one’s own perspective.